2021
DOI: 10.1177/00936502211025907
|View full text |Cite
|
Sign up to set email alerts
|

Staying Tuned or Tuning Out? A Longitudinal Analysis of News-Avoiders on the Micro and Macro-Level

Abstract: European media landscapes have changed into high-choice environments. Additionally, research suggests an increasing number of people are staying away from the news (news-avoiders). In two studies, we approach the topic on the macro and micro-level. In Study 1, we analyze on the macro-level how news-avoiders in 18 EU countries have developed since the late 1980s and what role country variables play in this context. We use multilevel spline models to distinguish between two phases of technological advancement. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Prior to the Internet, most studies focused on news consumption more generally to examine the changing foci of audiences for television, radio and newspapers (Doolittle, 1979; Henke, 1985). However, as audiences have rapidly shifted towards digital content, greater priority has been placed on investigating news avoidance, per se, with the aim of understanding the paradox of why – despite dramatically increased news content and media choice in the past 20 years – news audiences appear to have been dwindling (Edgerly, 2022; Gorski & Thomas, 2021), including at the rural and regional level.…”
Section: Framing News Avoidancementioning
confidence: 99%
See 1 more Smart Citation
“…Prior to the Internet, most studies focused on news consumption more generally to examine the changing foci of audiences for television, radio and newspapers (Doolittle, 1979; Henke, 1985). However, as audiences have rapidly shifted towards digital content, greater priority has been placed on investigating news avoidance, per se, with the aim of understanding the paradox of why – despite dramatically increased news content and media choice in the past 20 years – news audiences appear to have been dwindling (Edgerly, 2022; Gorski & Thomas, 2021), including at the rural and regional level.…”
Section: Framing News Avoidancementioning
confidence: 99%
“…There too has been growing interest in those who do not engage with news (Edgerly, 2022;Karlsen et al, 2020;Trilling & Schoenbach, 2013). Positioned mainly as non-readers by media researchers since the mid twentieth century (see especially Poindexter, 1979) and considered to have a general apathy towards politics and public life, the focus has now moved to digital media practices, with terms such as news avoidance dominating the lexicon (Gorski & Thomas, 2021). Much of this research tends to focus on those who actively or intentionally resist or reject the news (see Villi et al, 2021) or have been incidentally exposed to news as opposed to being a regular or willing news consumer of a particular platform or news service.…”
Section: Introductionmentioning
confidence: 99%
“…A common view is that news avoidance, whether intentional or unintentional, is an offset to “news exposure” mechanism of journalism, which is associated with disinterest in politics (Edgerly, 2022) and results in the damage of the informed foundation of democracy (Skovsgaard and Andersen, 2019). On the other hand, despite the increasing number of news-avoiders with the expansion of the internet (Gorski and Thomas, 2022), some of the intentional news avoidance also reflect people’s tendency to manage and control their news consumption (Aharoni et al, 2020), thus indicating the existence of critical audiences in the research of intentional news avoidance. Previous qualitative research shows that those who purposefully limit their news consumption tend to be calmer, hold a constructive attitude, and actively participate in public political life (Woodstock, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In contrast, they found that the wife showed an increase in regulatory tendencies and that her mood had the tendency to move away from her husband's following the birth of their child. Researchers have also used multilevel spline models to examine differences in the number of individuals who avoid the news across a 20+ year time span in the European Union, comparing use across timeframes when people generally received their news from television, radio, and newspapers versus the internet (Gorski & Thomas, 2021).…”
Section: Rupturesmentioning
confidence: 99%